Avaliação fitoquímica e de atividades antioxidantes de seis diferentes genótipos de Ananas sp - Oliveira, Judá Ben Hur de (2022)
In recent years, Brazil has been standing out more and more in the cultivation and production of pineapple, and showing itself as one of the largest producers and exporters in the world. Belonging to the Bromeliaceae family, pineapple is native to tropical and subtropical regions in the Americas. The pineapple varieties, which are intended for commercialization of the fruit for consumption in natura or processed, belong to the species Ananas comosus. The objective of this work was to analyze and correlate the total contents of phenolic compounds, flavonoids and antioxidant activities in different varieties of Ananas comosus (L.) Merril. The assays used were based on the capture of levels of phenols and flavonoids, in addition to the antioxidant activity, by the methods of ABTS, DPPH and Iron ion chelator. The evaluation of correlations and description of the variance and covariance between the different analyzed variables were also performed. Pearson's correlation analysis and principal components analysis (PCA) were used, respectively. The levels of phenolic compounds averaged between 64.41 mg.g-1 and 226.22 mg.g-1 , with emphasis on EC-121 (226.22 mg.g-1 ) and Pérola (163.87 mg.g-1 ). The bark was not a relevant part in the accumulation of phenolic compounds. The EC-200, EC-118, EC-88 and Pérola genotypes were the ones that stood out in terms of flavonoid contents. As for the antioxidant assays, the most promising genotypes are EC 200, EC 118, EC 121, Vitória and Pérola, which despite their low activity in some assays, showed high inhibition activity in others. Concluding that pineapple genotypes can be used not only for consumption, but also as a source of healthy biochemical compounds.